On the observability of ownership retention by entrepreneurs with private information in the market for new issues* - CONROY, ROBERT; HUGHES, JOHN S. (Contemporary Accounting Research, 1989)
Abstract. The analysis in this paper considers the effects of relaxing regulations that ensure that the proportions of ownership retained by entrepreneurs in new issues are observable to investors. Entrepreneurs, endowed with full ownership of their firms and private information concerning future prospects, seek to share risks with investors able to diversify those risks away. There is a trade‐off for entrepreneurs receiving good news between shedding risk and having their shares undervalued by uninformed investors. In equilibrium, an entrepreneur with good news either retains full ownership or sells a portion of his shares at the same price offered by an entrepreneur with bad news. The price in the latter case reflects rational expectations by investors as to the proportion of ownership retained by the entrepreneur conditional on his news. Only in certain cases are Pareto orderings possible across regimes in which ownership retention is either observable or unobservable. Implications for securities regulation are discussed. Résumé. Les auteurs s'intéressent dans leur analyse aux conséquences de l'assouplissement de la réglementation voulant que la proportion de titres retenue par les entrepreneurs dans les nouvelles émissions soit observable pour les investisseurs. Les entrepreneurs qui ont la propriété exclusive de leur entreprise et qui disposent d'une information privilégiée au sujet des ses perspectives d'avenir cherchent à partager leurs risques avec des investisseurs capables de diversifier ces risques de manière à les minimiser. Lorsque l'information est positive, l'entrepreneur fait face à un compromis entre le partage du risque et la sous‐évaluation de ses titres par les investisseurs non informés. En situation d'équilibre, l'entrepreneur qui détient une information positive conserve la totalité des titres ou en vend une fraction au prix qu'offrirait un entrepreneur détenant de l'information négative. Le prix, dans ce dernier cas, reflète les attentes rationnelles des investisseurs quant à la proportion des titres conservée par l'entrepreneur, en fonction de l'information dont il dispose. L'application des classements de Pareto n'est possible que dans certains cas seulement dans des situations où la proportion de titres conservée est soit observable soit non observable. Les auteurs traitent des conséquences des résultats de leurs recherches sur la réglementation relative aux valeurs mobilières.